Role of Ataxia Telangiectasia Mutated in the Repair of Magnetite Nanoparticles Induced Double Strand Breaks Associated with Heterochromatin - Mounir, Mie Mohamed (AUC Knowledge Fountain, 2021)
Magnetite nanoparticles particulate matter pollution is escalating in large cities like New Mexico, Manchester city, Cairo, and New Delhi. Combustion derived Magnetite nanoparticles was found deposited in internal vital organs of deceased residents of urban areas. A great deal of research focused on the genotoxic and cytotoxic effects of Magnetite Nanoparticles (MNPs). In our work we focus on the mechanisms employed in DNA repair of higher chromatin structures. We employed the sensitive analysis of anti γ-H2AX to detect and monitor the repair of DSBs following exposure to MNPs. A 2- fold delay in the repair of heterochromatin associated DSBs in comparison with euchromatin was detected. The slow repairing heterochromatin γ-H2AX foci were found almost exclusively at the peripheries of the chromocenters, marking the physical barrier that the compacted chromatin impose on the extension of the DNA repair signal. The heterochromatin associated DSBs constituted 10.3% of the original DSBs initially introduced, similarly the fraction of DSBs that requires ATM for DNA repair constitutes about 10-25%. No visible structural changes happened in heterochromatin chromocentres during the repair. On Inhibition of ATM a repair defect in the heterochromatin DSBs was evident post exposure to MNPs, comparable to the repair defect imparted after exposure to Neocarzinostatin (NCS). This repair defect could not be compensated by other PIKKs (ATR and DNA PKcs). Therefore, ATM is essential for the transient relaxation of the nucleosome to allow the extension of the DNA repair machinery. Individuals lacking a functional ATM protein, will lack the ATM dependent chromatin relaxation and extension of repair machinery. So, they would be prone to accumulate mutations in the repetitive satellite pericentromeres, centromeres and telomeres, imparting a MNPs sensitivity to those individuals.